Temporalpräpositionen in Polsk-dansk Ordbog von Jan A. Nowak - Jarosz, Józef (Folia Scandinavica Posnaniensia, 2010)
This paper presents results of a research study the objective of which was to analyse entries of Polish temporal propositions and their Danish equivalents. Having considered specific features of the examined class of words, the following three parameters were chosen as quality references: number of exemplary phrases, number of Danish preposition equivalents and order of examples given in the entry. Excerpts of dictionary articles were additionally compared with results of other translation confrontation.